Enhanced pre-ictal cortical responsivity in migraine patients assessed by visual chirp stimulation. (August 2020) - Perenboom, Matthijs JL; van de Ruit, Mark; Zielman, Ronald; van den Maagdenberg, Arn MJM; Ferrari, Michel D; Carpay, Johannes A; Tolner, Else A
Background: Migraine is associated with altered sensory processing and cortical responsivity that may contribute to susceptibility to attacks by changing brain network excitability dynamics. To gain better insight into cortical responsivity changes in migraine we subjected patients to a short series of light inputs over a broad frequency range ("chirp" stimulation), designed to uncover dynamic features of visual cortex responsivity. Methods: EEG responses to visual chirp stimulation (10–40 Hz) were measured in controls (n = 24) and patients with migraine with aura (n = 19) or migraine without aura (n = 20). Average EEG responses were assessed at (i) all EEG frequencies between 5 and 125 Hz, (ii) stimulation frequencies, and (iii) harmonic frequencies. We compared average responses in a low (10–18 Hz), medium (19–26 Hz) and high (27–40 Hz) frequency band. Results: Responses to chirp stimulation were similar in controls and migraine subtypes. Eight measurements (n = 3 migraine with aura; n = 5 without aura) were assigned as "pre-ictal", based on reported headache within 48 hours after investigation. Pre-ictally, an increased harmonic response to 22–32 Hz stimulation (beta band) was observed ( p = 0.001), compared to interictal state measurements. Conclusions: We found chirp responses to be enhanced in the 48 hours prior to migraine headache onset. Visual chirp stimulation proved a simple and reliable technique with potential to detect changes in cortical responsivity associated with the onset of migraine attacks.